How much does media portrayal matter? The impact of a polarized media on politics and political ideology in the United States - Hall, Kaley, author; Stenson, Peter, advisor; Berg, Marni, committee member; Buckley, Cara, committee member (Colorado State University. Libraries, 2025)
Background: The American political scene continues to grow more polarized, particularly among the two major political parties. Republicans and Democrats dislike, demonize, and look down upon each other more than ever before. This is partially due to the media and its portrayal of the two parties as well as its increasingly apocalyptic messages about one party or the other. The goal of this research is to shed light on how the media portrays each major political party from 2020 to present day and the devastating impact this portrayal has had on American politics and on the American people. Purpose: The purpose of this research is to examine both traditional media forms such as print and cable news as well as contemporary media forms such as social media to determine their impact on politics and individuals' political ideology. The following questions will guide this research: 1) What are the differences in how the media portrays the two major political parties? 2) What are the effects of this difference in the portrayal of the two parties on United States politics? 3) What are the effects of this difference in portrayal of the two parties on the general population and individual political ideology? Findings: This study found that bias in the media manifests differently depending on whether the news outlet is left leaning or right leaning. It also found that this bias has a significant impact on the American public; particularly when it comes to polarization and an overall negative perception of others in the opposite party. This polarization among the people is reflected in the increasing division among lawmakers and political figures.
Keywords: media bias; bias in the media; American politics; Kirk, Charlie; political violence; government shutdown; Republican; Democrat